The natural metabolite 4-cresol improves glucose homeostasis and enhances beta-cell function - Brial,F; Alzaid,F; Sonomura,K; Kamatani,Y; Meneyrol,K; Le,Lay A; Pean,N; Hedjazi,L; Sato,T-A; Venteclef,N; Magnan,C; Lathrop,M; et al. (Cell Reports, 2020)
Exposure to natural metabolites contributes to the risk of cardiometabolic diseases (CMDs). Through metabolome profiling, we identify the inverse correlation between serum concentrations of 4-cresol and type 2 diabetes. The chronic administration of non-toxic doses of 4-cresol in complementary preclinical models of CMD reduces adiposity, glucose intolerance, and liver triglycerides, enhances insulin secretion in vivo, stimulates islet density and size, and pancreatic β-cell proliferation, and increases vascularization, suggesting activated islet enlargement. In vivo insulin sensitivity is not affected by 4-cresol. The incubation of mouse isolated islets with 4-cresol results in enhanced insulin secretion, insulin content, and β-cell proliferation of a magnitude similar to that induced by GLP-1. In both CMD models and isolated islets, 4-cresol is associated with the downregulated expression of the kinase DYRK1A, which may mediate its biological effects. Our findings identify 4-cresol as an effective regulator of β-cell function, which opens up perspectives for therapeutic applications in syndromes of insulin deficiency.